A comparison of the diagnostic capabilities of the ratio of acceleration time to total left ventricular ejection time (AT/ET) in determining the severity of aortic stenosis in patients with bicuspid and tricuspid aortic valve: retrospective comparative study - Vladlen V. Bazylev; Ruslan M. Babukov; Fedor L. Bartosh; Alena V. Levina; Artur I. Mikulyаk (КардиоСоматика, 2023)
Objective. We aimed to compare the diagnostic capabilities of the ratio of acceleration time to total left ventricular ejection time (AT/ET) in determining the severity of aortic stenosis (AS) in patients with bicuspid and tricuspid aortic valves (AV).